Japan and The Pacific Rim - Dean W. Collinwood (McGraw Hill, 2008)
In this edition are background essays and important statistic for Japan and each of the coutries that make up the Pacific Rim. The essys examine the social, political, and economic significance of this countries in this widespread geographic area.